The anionic synthesis and characterization of hydroxy-terminated polybutadiene (HTPB) - De la Porte, Andries Jacobus (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1981.